2017
DOI: 10.1158/1541-7786.mcr-16-0242-t
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 or HDAC1 Inhibition Reverses Multiple Myeloma–Induced Epigenetic Suppression of Osteoblast Differentiation

Abstract: In multiple myeloma (MM) osteolytic lesions rarely heal because of persistent suppressed osteoblast differentiation resulting in a high fracture risk. Herein, chromatin immunoprecipitation analyses reveal that MM cells induce repressive epigenetic histone changes at the Runx2 locus that prevent osteoblast differentiation. The most pronounced MM-induced changes were at the Runx2-P1 promoter, converting it from a poised bivalent state to a repressed state. Previously it was observed that MM induce the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 48 publications
(62 reference statements)
2
91
0
Order By: Relevance
“…Direct MM‐BMSC interactions and soluble cytokine‐mediated cross‐talk combine to alter BMSCs into a chronically pro‐adipogenic and senescence‐like phenotype with suppressed osteogenesis . In fact, the observations that myeloma‐exposed BMSCs (MM‐BMSCs) undergo long‐term phenotypic changes in the absence of myeloma signals suggested that epigenetic modifications direct the cellular reprogramming and osteogenic suppression of MM‐BMSCs . In such a way, myeloma‐induced alterations of chromatin structure in BMSCs can be epigenetically propagated as a heritable memory regulating the transcriptional signature in the absence of continuous MM signals.…”
Section: Introductionmentioning
confidence: 99%
“…Direct MM‐BMSC interactions and soluble cytokine‐mediated cross‐talk combine to alter BMSCs into a chronically pro‐adipogenic and senescence‐like phenotype with suppressed osteogenesis . In fact, the observations that myeloma‐exposed BMSCs (MM‐BMSCs) undergo long‐term phenotypic changes in the absence of myeloma signals suggested that epigenetic modifications direct the cellular reprogramming and osteogenic suppression of MM‐BMSCs . In such a way, myeloma‐induced alterations of chromatin structure in BMSCs can be epigenetically propagated as a heritable memory regulating the transcriptional signature in the absence of continuous MM signals.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Gfi1 knockdown in MC4 cells blocked MM-induced recruitment of HDAC1and EZH2 to Runx2, acquisition of repressive chromatin architecture, and suppression of osteoblast differentiation(Adamik et al, 2017). Elevated Gfi1 blocks Runx2 induction by osteogenic signals.…”
mentioning
confidence: 95%
“…The polycomb group protein enhancer of zeste homologue 2 (Ezh2), a histone lysine methyltransferase associated with transcriptional repression, catalyzes the addition of methyl groups to histone H3 at Lys 27 (H3K27me3) in target genes involved in numerous cellular processes, predominantly leading to gene repression . There is evidence that loss or inhibition of Ezh2 leads to enhanced osteogenic but inhibited adipogenic differentiation of bone marrow‐derived mesenchymal stem cells (BMSCs) both from rodents and humans, as well as in murine pre‐osteoblastic cell line MC3T3 . Expression of Ezh2 suppresses the osteogenic genes and ligand‐dependent signaling pathways (eg, WNT, PTH, and BMP2) to favor adipogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%